The Role of Teachers in Guiding the Science Learning Process at SDN Ie Jeureuneh,Trumon Tengah, Aceh Selatan: A Qualitative Study - MISDARWATI WATI (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The role of teachers in guiding the process of learning Natural Science (IPA) is essential for fostering curiosity, critical thinking skills, and students' understanding of scientific concepts. This study aims to explore the role of teachers at SDN Ie jeureuneh,Trumon Tengah, Aceh Selatan in guiding the IPA learning process, including teaching strategies, challenges faced, and solutions implemented. This research utilizes a qualitative approach through a case study method. Data collection was carried out through classroom observations, interviews with teachers and students, and document analysis such as lesson plans (RPP). The results indicate that teachers employ various methods, including inquiry-based learning, contextual approaches, and simple experiments to enhance student engagement. However, limited resources, lack of professional training, and varying student interests pose significant challenges. This study emphasizes the importance of institutional support in providing resources, training, and collaborative platforms for teachers. Recommendations include enhancing teacher training programs, providing context-appropriate teaching materials, and involving the community in the educational process. These steps are crucial to ensure effective science learning and inspire students to explore scientific phenomena with enthusiasm